Natural history and comorbidities of generalised and partial lipodystrophy syndromes in Spain - Fernández-Pombo, Antía; Sánchez-Iglesias, Sofía; Castro-Pais, Ana I.; Ginzo-Villamayor, Maria José; Cobelo-Gómez, Silvia; Prado-Moraña, Teresa; Díaz-López, Everardo Josué; Casanueva, Felipe F.; Loidi, Lourdes; Araújo-Vilar, David (Frontiers in Endocrinology, 2023)
The rarity of lipodystrophies implies that they are not well-known, leading to delays in diagnosis/ misdiagnosis. The aim of this study was to assess the natural course and comorbidities of generalised and partial lipodystrophy in Spain to contribute to their understanding. Thus, a total of 140 patients were evaluated (77.1% with partial lipodystrophy and 22.9% with generalised lipodystrophy). Clinical data were collected in a longitudinal setting with a median follow-up of 4.7 (0.5-17.6) years. Anthropometry and body composition studies were carried out and analytical parameters were also recorded. The estimated prevalence of all lipodystrophies in Spain, excluding Köbberling syndrome, was 2.78 cases/million. The onset of phenotype occurred during childhood in generalised lipodystrophy and during adolescence-adulthood in partial lipodystrophy, with the delay in diagnosis being considerable for both cohorts. There are specific clinical findings that should be highlighted as useful features to take into account when making the differential diagnosis of these disorders. Patients with generalised lipodystrophy were found to develop their first metabolic abnormalities sooner and a different lipid profile has also been observed. Mean time to death was 83.8 ± 2.5 years, being shorter among patients with generalised lipodystrophy. These results provide an initial point of comparison for ongoing prospective studies such as the ECLip Registry study.